1994
DOI: 10.1007/bf02015454
|View full text |Cite
|
Sign up to set email alerts
|

The echogenic thalamus in hypoxic ischaemic encephalopathy

Abstract: This paper reports 16 term infants in whom an echogenic thalamus was identified on cranial ultrasonography. Fourteen of the patients suffered severe birth asphyxia. The prognostic significance of this finding and the underlying pathogenesis is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In our current study all thalamic abnormalities were unilateral and focal; the mean 5 min Apgar score of these infants was 8, none appeared encephalopathic and they had a normal neurological examination 9. Therefore, it is unlikely that these changes were due to global hypoxia-ischaemia in which bilateral more diffuse thalamic and/or basal ganglia abnormalities would be expected 4851. However, infarction in the territory of the perforator arteries could explain the observation, such perforator strokes not always being associated with acute symptoms 52.…”
Section: Discussionmentioning
confidence: 45%
“…In our current study all thalamic abnormalities were unilateral and focal; the mean 5 min Apgar score of these infants was 8, none appeared encephalopathic and they had a normal neurological examination 9. Therefore, it is unlikely that these changes were due to global hypoxia-ischaemia in which bilateral more diffuse thalamic and/or basal ganglia abnormalities would be expected 4851. However, infarction in the territory of the perforator arteries could explain the observation, such perforator strokes not always being associated with acute symptoms 52.…”
Section: Discussionmentioning
confidence: 45%
“…3A). The presence of hyperechogenicity in the structures on sonography portends a very poor outcome [Cabañas et al, 1991;Connolly et al, 1994]. Barkovich [1995].…”
Section: Sonographymentioning
confidence: 99%
“…Therefore, it is very difficult to assess the brains of term infants for watershed injury by this technique; indeed, we have not seen an abnormal sonogram in a patient subsequently shown to have a pure watershed injury. Sonography is more useful in those profound hypoperfusion episodes in which the deep gray matter nuclei are injured, as hyperechogenicity of those structures and often in the periventricular white matter can also be detected [Cabañas et al, 1991;Connolly et al, 1994;Rutherford et al, 1994]. Rutherford et al [1994] have reported that the presence of hyperechogenicity in the basal ganglia or an initial featureless sonogram predicts central motor deficits at 1 year of age.…”
Section: Sonographymentioning
confidence: 99%
“…In normal neonates, the basal ganglia and thalami are intermediate to low in echogenicity. Despite allegations that US underestimates the extent of injury to the deep gray matter, 34 thalamic injury may be documented with US as subtle or pronounced areas of increased echogenicity that may be unilateral or bilateral and are most often diffuse [60][61][62] (Fig. 14E); these areas are particularly conspicuous when linear US images or magnified views are used.…”
Section: Basal Gangliamentioning
confidence: 97%